A mixed-method analysis on students’ critical thinking and problem solving skill development in Malaysian public universities - Rodzalan, Shazaitul Azreen (IOP Publishing, 2018)
Employers nowadays are looking for potential fresh graduates who are able to think outside the box, so that they can produce with quality works. However, they are failed to do so and this situation result in high unemployment rate among graduates, mainly in Malaysia. With this concern, this paper aims to examine students’ critical thinking and problem solving skill development after undergoing an industrial training. Further investigation also examines relationship of the skill development with respect to supervisors’ leadership styles. Both quantitative and qualitative methods were employed, with three hypotheses were tested. A total of 2,000 undergraduate students from six public universities in Malaysia involved in pre- and post-training surveys. In assessing students’ critical thinking and problem solving skill, eleven items in Belbin inventory on Thinking role was used. Meanwhile, nine employers and twelve students were participated in the interviews and they were asked regarding their perception of industrial training in assisting the development of critical thinking and problem solving skill. Descriptive analysis (such as mean), paired samples t-test, correlation and content analysis were utilized for the data analysis. Overall, results reveal that students developed in their critical thinking and problem solving skill upon completion of the industrial training. The results also demonstrate that there is a relationship between transformational leadership style the skill development. The findings of this study provide the necessity for industrial training stakeholders to improve industrial training program, mainly by implementing appropriate leadership styles